HSCT FOR HEMOGLOBINOPATHIES - Costa, Thalita Cristina de Mello; Darrigo Junior, Luiz Guilherme; Vieira, Ana Karine; Albino, Cintia Delbem; Barros, George Maurício Navarro; Garcia, Julia Lopes; Fortunato, Laila Rigolin; Santos, Flavia Leite Souza; De Santis, Gil Cunha; Fonseca, Guilherme; Guerino-Cunha, Renato Luiz; Simões, Belinda Pinto (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION